Study of Electrical Conduction of Polyvinylalcohol Films Doped by 4-Dimethylaminobenzonitrile Molecule. (23rd March 2016) - Bougharraf, H.; Benallal, R.; Sahdane, T.; Kabouchi, B.
ABSTRACT: Films of pure and doped polyvinylalcohol (PVA) with 4-dimethylaminobenzonitrile (DMABN) molecule are prepared during the development of these films. The effect of UV irradiation and doping on electrical properties of PVA is investigated. We show that the system polymer-molecule has a certain photostability following UV irradiation. The variation of electrical current with temperature show two regions corresponding to different values of activation energy. The activation energies are changed from 0.22 to 0.47 eV, from 0.11 to 0.37 eV and from 0.13 to 0.29 eV for respectively undoped, doped and doped irradiated films. The analysis of I–V characteristics suggests that Schottky emission is the dominant charge transfer mechanism governed by complex of hydrogen bonding.